The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1088/0031-9155/54/14/n04
|View full text |Cite
|
Sign up to set email alerts
|

Absorption measurements on a new cone beam CT and IMRT compatible tabletop for use in external radiotherapy

Abstract: With the development of intensity-modulated radiotherapy (IMRT), intensity-modulated arc therapy (IMAT), volumetric single arc therapy (RapidArc) and cone beam CT (CBCT) in 3D conformal radiotherapy, a need for new homogeneous treatment tabletops has evolved. Therefore, a new homogenous carbon fibre rotatable treatment tabletop Contesse has been developed. The intension was to create a CT compatible treatment tabletop accommodating all the standard treatment areas without add-on devises or the need to reconfig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Currently available couches include: Sinmed Mastercouch (Sinmed, Reeuwijk, The Netherlands) [11], Siemens IGRT carbon fiber tabletop [12], MED-TEC (USA) couch, BrainLAB imaging couch top [13], iBEAM Evo couch top EP (Medical Intelligence, Germany) [14], Contesse tabletop (Candor Aps, Denmark) [15] Kvue IGRT couch top (Qfix Avondale, PA, USA) and Dignity Airplate (Oncolog Medical AB, Uppsala, Sweden). These new imaging carbon fiber couch tops are thicker than the traditional tennis racquet and hence may have clinically significant photon attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently available couches include: Sinmed Mastercouch (Sinmed, Reeuwijk, The Netherlands) [11], Siemens IGRT carbon fiber tabletop [12], MED-TEC (USA) couch, BrainLAB imaging couch top [13], iBEAM Evo couch top EP (Medical Intelligence, Germany) [14], Contesse tabletop (Candor Aps, Denmark) [15] Kvue IGRT couch top (Qfix Avondale, PA, USA) and Dignity Airplate (Oncolog Medical AB, Uppsala, Sweden). These new imaging carbon fiber couch tops are thicker than the traditional tennis racquet and hence may have clinically significant photon attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, RapidArc was developed mainly by the optimization of the multi-leaf collimators shape, the change of the dose rate delivery and the rotation of the gantry [5][6][7][8] . It was based on the volumetric modulated arc therapy technique and can obtain the similar distribution of the fixed IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications show a significant increase in surface dose when beams first transit carbon fiber couch tops at either normal or oblique incidence 6,[18][19][20][21][22][23][24] and show these to be larger than for the mylar-covered tennis racket couch top 25 (Table I). While there is some consistency in the methodology used for measuring and reporting the dose attenuation, there are large variations in the methodology used to determine and report the surface dose.…”
Section: A1 Impact On Skin Dosementioning
confidence: 99%
“…37 Several reports showed that couch attenuation can increase 4-fold as the beam angle ranges from 0 • to 70 • . 14,[21][22][23] As pointed out by McCormack et al, manually correcting the central axis dose for this attenuation may lead to an overdose or underdose to regions of the patient where the beam transited a different part of the couch top. 21 This is demonstrated in Fig.…”
Section: A2 Impact On Attenuationmentioning
confidence: 99%